ASSESSMENT OF STUDENTS' DENTAL HEALTH AND ITS RELATIONSHIP WITH STUDENTS' QUALITY OF LIFE - Ismatov Farrukh Aslidinovich (Research Focus International Scientific Journal, 2024)
This article discusses the problems of oral cavity diseases in students, including dental diseases and their impact on the quality of life, prevention, causes of the disease. In addition, the most effective solution for the prevention of these diseases is based on analysis and opinions that the main criterion is to follow a healthy lifestyle and hygiene.